An Empirical Study of Industrial Engineering Curriculum - Aamer, Ammar; Greene, Bradley; Toney, Chad (International Journal of Industrial Engineering and Management, 2017)
The purpose of this paper is to identify current and future Industrial Engineering (IE) trends in graduate-level course curriculum. Top ten US industrial engineering schools were benchmarked, as indicated by US News and World Report. Different IE topics were categorized into several categories- Engineering Economics,Human Factors, Information Technology, Manufacturing Processes, Manufacturing Systems, Operations Research, Quality Control, Simulation, Statistics, and Integration of subject areas.The study of the Top Ten Graduate Programs in Industrial Engineering, according to US News and World Report, showed that these schools are focusing on Manufacturing Systems and how the other tools of Industrial Engineering relate to manufacturing. The implication of this study is that teaching methods should reflect the emphasis on Manufacturing Systems and incorporate real world problems. Article history: Received (04.11.2016); Revised (28.02.2017); Accepted (20.03.2017)